VILLAGE FUND PLANNING FOR COMMUNITY EMPOWERMENT IN KEBONSARI VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY - Salsabilla Putri, Diva; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the planning of village funds for community empowerment, especially in Kebonsari Village, Indonesia.  Method: The method used is qualitative description with data collection techniques through interviews, observation, and documentation. The informants involved in this study consisted of the Village Secretary, Village Planning Clerk, Community Elements, and village officials involved in village fund planning. Results:  The results showed that the planning of the Village Fund in Kebonsari in Indicators [1] targets are determined from village deliberations by considering proposals from residents and priority scales to ensure that the programs run are in accordance with the needs. [2] Village fund planning policies are based on local government regulations and authorize villages to manage fund allocations independently to support community empowerment. [3] Planning procedures are carried out systematically through the stages of observation, deliberation, preparation of the RKP, and budgeting in the APBDes.  [4] Programs are focused on infrastructure development and community empowerment. [5] For the biata budget, it is designed based on real needs and takes into account the efficiency of the use of funds including bookmarking the remaining budget for programs in the following year. The whole process is transparent and participatory in line with George Robert Terry's theory.  Novelty: The novelty of this research lies in the analysis of Village Fund Planning for the 2025 fiscal year in Kebonsari Village comprehensively by linking George Robert Terry's theory and empirical data from interviews and highlighting the practice of transparency in the utilization of remaining funds for the following year's program which is rarely given in previous studies.